Dimensi Budaya dalam Syair Sidi Djamadi - Yosi Wulandari; Fitri Merawati; Indah Arohmawati (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2020)
Syair Sidi Djamadi is one of the old literary legacies of the Minangkabau which contains interesting lessons and knowledge to know. One of the things that can be expressed in these verses is the cultural dimension. The purpose of this study is to describe the cultural dimension in Sidi Djamadi's poetry. The research method used is descriptive qualitative. The research object is the cultural dimension and the research subject of Sidi Djamadi's poetry. The results of this study indicate that Sidi Djamadi's poetry is not only identical with religious advice and advice, but also contains a cultural dimension that can describe the Minangkabau people. The dominant cultural dimension is the uncertainty / avoidance aspect. This illustrates that the Minangkabau people tend to choose in safe / normal conditions rather than do something that is not clear or its usefulness is not yet known. Apart from that, the cultural dimensions that were found to be dominant were holding fast, uncertainty, avoiding and stopping the bad.